2019
DOI: 10.4143/crt.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Significance of p38 Isoforms (p38α, p38β, p38γ, p38δ) in Head and Neck Squamous Cell Carcinoma: Comparative Serum Level Evaluation and Design of Novel Peptide Inhibitor Targeting the Same

Abstract: In this study, first time estimated the levels of p38 MAPK isoforms in the serum of HNSCC. It can be concluded that p38 MAPK isoforms can be a diagnostic and prognostic marker for HNSCC and p38δ as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…Perineural invasion and lymphovascular invasion were widely investigative predictors for poor prognosis in oral SCC patients, strongly correlating with tumor site, tumor stage, and disease stage [26,27]. It was noted perineural invasion and lymphovascular invasion were more frequent in NPC survivors, the finding was a little out of our expectation.…”
Section: Discussionmentioning
confidence: 85%
“…Perineural invasion and lymphovascular invasion were widely investigative predictors for poor prognosis in oral SCC patients, strongly correlating with tumor site, tumor stage, and disease stage [26,27]. It was noted perineural invasion and lymphovascular invasion were more frequent in NPC survivors, the finding was a little out of our expectation.…”
Section: Discussionmentioning
confidence: 85%
“…To the best of our knowledge, very few studies measured serum levels of MKP-1 and p-p38 when investigating their roles in the development of a specific disease, since they are intracellular signalling proteins. But serum MKP-1 and p38 levels were really detected by ELISA in some studies [34,35], Our study showed that the difference of serum MKP-1 levels between AIH and healthy people AIH was also significant. By blocking Tim-3, p38 was activated and MKP-1 was inhibited, thus upregulating IL-17A expression and promoting the development of AIH.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, p38 can both sensitize some tumor types to chemotherapy and facilitates resistance in others, where p38 inhibition may be beneficial in therapeutic approaches [ 136 , 176 , 177 , 178 ]. Of note, p38 MAPK activity and increased expression have been linked to the progression of breast cancer, prostate cancer, bladder cancer, liver cancer, lung cancer, thyroid cancers, leukemia, and many more [ 35 , 135 , 179 , 180 ]. In solid tumor biology, the p38 MAPK pathway has been shown to promote tumor cell survival and angiogenesis during periods of hypoxia, reoxygenation, and nutrient deficiency by inducing expression of metalloproteinases and vascular endothelial growth factor A (VEGFA) [ 135 ].…”
Section: Pathophysiological Implications Of Mkk3/6-dependent P38 Mapksmentioning
confidence: 99%